Tafsir Tahlili Q.S An-Nisa Ayat 58-63; Dasar-Dasar Pemerintahan - Sidqy, Mukhrij; Taqwa, Hafidz (Ikatan Dai Indonesia, 2024)
The aim of this research is to obtain a concrete understanding of the concept of governance or leadership and its correlative relationship with society form QS. An-Nisa (4): 58-63. Government or leadership is an urgent theme for societal or national life, and the Qur'an, as the holy book that serves as the ultimate guidance for Muslims, has extensively discussed the theme of leadership. Therefore, it is essential for Muslims to refer to the Qur'an to understand this crucial theme and subsequently apply it. The verses that discuss leadership, which are the object of this study, are QS. An-Nisâ (4): 58-63. One of the key points in these verses is Amanah (trustworthiness), which is an absolute requirement for the eligibility of a leader. However, this quality is increasingly rare due to the frequent abuse of power. Another point addressed is how to deal with the various dynamics and conflicts that arise in leadership. This research is a descriptive qualitative study using a literature review of tafsir (Qur'anic exegesis) as the primary source. The literature is analyzed and compared with other tafsir sources, employing the muqaranah (comparative) method.